Methane fluxes in soils with pasture covers in the North of Colombia - Espinosa Carvajal, Manuel; Contreras Santos, Jose Luis; Torres, Jorge Cadena; Martínez Atencia, Judith del Carmen; Jaramillo Barrios, Camilo Ignacio; Hurtado, María del Pilar (Agronomía Mesoamericana, 2020)
Introduction. Traditional livestock production systems in Colombia are based on the establishment of pastures on large tracts of land, which generate greenhouse gases such as methane. Objective. The objective of the present study was to monitor the monthly methane fluxes that occur in meadows with three soil covers and three levels of nitrogen fertilization. Materials and methods. Methane fluxes were monitored for a year from November 2014 to November 2015, on a Vertic Endoaquepts soil, placed in the middle valley of the Sinu river, Colombia. A full block design was used at random, arranged in divided plots, with two replications. The main plots constituted of two grasses (Brachiaria humidicola CIAT679 and Panicum maximum cv. Tanzania) and one with bare soil, and the subplots by three nitrogen fertilization levels (0, 150, 300 kg N ha-1). Additionally, soil physicochemical properties were evaluated. Results. During most of the year (rainy and dry season) methane oxidation occurred, associated with the loam texture and porosity of the soil in the study area, which allowed the free diffusion of gases in the soil. Correlation analyzes showed a close relationship between methane fluxes, porosity, moisture, soil bulk density, and ambient temperature, suggesting these parameters as the main factors that affect the monthly methane flow. Conclusions. Methane fluxes were independent of the type of plant material and nitrogen fertilization evaluated. These flows depended on the time of year (dry and rainy) and exhibited a negative annual balance in the study area, which suggests that these systems have the conditions to behave as methane sinks during most of the year.